HTQC: a fast quality control toolkit for Illumina sequencing data - Yang Xi; Liu Di; Liu Fei; Wu Jun; Zou Jing; Xiao Xue; Zhao Fangqing; Zhu Baoli (BMC Bioinformatics, 2013)
Abstract Background Illumina sequencing platform is widely used in genome research. Sequence reads quality assessment and control are needed for downstream analysis. However, software that provides efficient quality assessment and versatile filtration methods is still lacking. Results We have developed a toolkit named HTQC – abbreviation of High-Throughput Quality Control – for sequence reads quality control, which consists of six programs for reads quality assessment, reads filtration and generation of graphic reports. Conclusions The HTQC toolkit can generate reads quality assessment faster than existing tools, providing guidance for reads filtration utilities that allow users to choose different strategies to remove low quality reads.